Differential Metabolism of a Two-Carbon Substrate by Members of the Paracoccidioides Genus - Baeza, Lilian C.; da Mata, Fabiana R.; Pigosso, Laurine L.; Pereira, Maristela; de Souza, Gustavo H. M. F.; Coelho, Alexandre S. G.; de Almeida Soares, Célia M. (Frontiers in Microbiology, 2017)
The genus Paracoccidioides comprises known fungal pathogens of humans and can be isolated from different infection sites. Metabolic peculiarities in different members of the Paracoccidioides led us to perform proteomic studies in the presence of the two-carbon molecule acetate, which predominates in the nutrient-poor environment of the phagosome. To investigate the expression rates of proteins of different members of Paracoccidioides, including one isolate of P. lutzii (Pb01) and three isolates of P. brasiliensis (Pb03, Pb339, and PbEPM83), using sodium acetate as a carbon source, proteins were quantified using label-free and data-independent liquid chromatography-mass spectrometry. Protein profiles of the isolates were statistically analyzed, revealing proteins that were differentially expressed when the fungus was cultivated in a non-preferential carbon source rather than glucose. A total of 1160, 1211, 1280, and 1462 proteins were reproducibly identified and relatively quantified in P. lutzii and the P. brasiliensis isolates Pb03, Pb339, and PbEPM83, respectively. Notably, 526, 435, 744, and 747 proteins were differentially expressed among P. lutzii and the P. brasiliensis isolates Pb03, Pb339, and PbEPM83, respectively, with a fold-change equal to or higher than 1.5. This analysis revealed that reorganization of metabolism occurred through the induction of proteins related to gluconeogenesis, glyoxylic/glyoxylate cycle, response to stress, and degradation of amino acids in the four isolates. The following differences were observed among the isolates: higher increases in the expression levels of proteins belonging to the TCA and respiratory chain in PbEPM83 and Pb01; increase in anaerobic metabolism in Pb01; utilization of cell wall components for gluconeogenesis in Pb03 and PbEPM83; and increased β-oxidation and methylcitrate cycle proteins in Pb01and PbEPM83. Proteomic profiles indicated that the four isolates reorganized their metabolism in different manners to use acetate as a carbon source.